Solid State Adaptive Rotor Using Postbuckled Precompressed, Bending-Twist Coupled Piezoelectric Actuator Elements. (5th April 2012) - Barrett, Ronald M.; Barnhart, Ryan
Abstract : This paper is centered on a new actuation mechanism which is integrated on a solid state rotor. This paper outlines the application of such a system via a Post-Buckled Precompression (PBP) technique at the end of a twist-active piezoelectric rotor blade actuator. The basic performance of the system is handily modeled by using laminated plate theory techniques. A dual cantilevered spring system was used to increasingly null the passive stiffness of the root actuator along the feathering axis of the rotor blade. As the precompression levels were increased, it was shown that corresponding blade pitch levels also increased. The PBP cantilever spring system was designed so as to provide a high level of stabilizing pitch-flap coupling and inherent resistance to rotor propeller moments. Experimental testing showed pitch deflections increasing from just8 ° peak-to-peak deflections at 650 V/mm field strength to more than26 ° at the same field strength with design precompression levels. Dynamic testing showed the corner frequency of the linear system coming down from 63 Hz (3.8/rev) to 53 Hz (3.2/rev). Thrust coefficients manipulation levels were shown to increase from 0.01 to 0.028 with increasing precompression levels. The paper concludes with an overall assessment of the actuator design.